Chronic urticaria: tools to aid the diagnosis and assessment of disease status in daily practice. (June 2015) - Weller, K.; Zuberbier, T.; Maurer, M.
Abstract: This article focuses on practical considerations for the optimal management of chronic urticaria (CU) with regard to the tools and instruments that are currently available to assist in the diagnosis and assessment of this condition before and during treatment.